2017
DOI: 10.21164/pomjlifesci.247
|View full text |Cite
|
Sign up to set email alerts
|

Rola aktywności fizycznej w leczeniu pacjentów z przewlekłą chorobą nerek

Abstract: Constant improvements in treatment options for end stage renal disease leads to increasing numbers of patients qualified for renal transplantation. The best results are obtained with pre-emptive transplantation allowing avoidance of dialysis. The most common cause of death in patients awaiting kidney transplantation is cardiovascular disease. Every second dialysis death is a consequence of cardiovascular disease. Hypertension, atherosclerosis, hyperlipidemia and obesity are commonly diagnosed. Numerous scienti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 9 publications
2
10
0
Order By: Relevance
“…The results of the present study showed that the most common cause of CKD in patients undergoing hemodialysis was hypertension (30%) followed by diabetes (26.8%). This result is consistent with the results of other studies [ 7 , 41 , 42 ].…”
Section: Discussionsupporting
confidence: 94%
“…The results of the present study showed that the most common cause of CKD in patients undergoing hemodialysis was hypertension (30%) followed by diabetes (26.8%). This result is consistent with the results of other studies [ 7 , 41 , 42 ].…”
Section: Discussionsupporting
confidence: 94%
“…Physical activity in hemodialysed patients is essential in prevention of cardiovascular incidents, improvement of biochemical test results and decreasing body mass. Professional rehabilitation programs would also provide safe methods to perform exercise, as patient medical history will be considered [38].…”
Section: Manuscriptmentioning
confidence: 99%
“…They avoid regular exercise, but are also reluctant to undertake daily tasks. A low level of professional activity and significantly reduced quality of life cause a lack of motivation to engage in everyday life activities, and this discourages patients from taking up physical activity [2,30,31].…”
Section: Physical Activitymentioning
confidence: 99%
“…For example, studies by Yamamoto et al demonstrated that the incidence of cardiovascular events was significantly lower in patients who regularly attended physical activity sessions during 3 years of dialysis [38]. Physical activity has a strong impact on mental health and can be used as non-pharmacological treatment, preventing depressive episodes and mood changes, which are significantly more frequent in dialysis patients [1,2,19,24,39,40].…”
Section: Physical Activitymentioning
confidence: 99%
See 1 more Smart Citation